Experimental studies of the influence of vigabatrin on the GABA system - Gram, L. (1989)
1 Studies of the influence of clinically relevant concentrations of vigabatrin on GABA-transaminase and on the release of endogenous GABA were performed in selectively cultured astrocytes and neurons. In addition, the two stereoisomers of vigabatrin were investigated separately. 2 The results indicated a preferential inhibition of neuronal GABA-transaminase by vigabatrin. 3 Only the (S)-form of vigabatrin seems to inhibit GABA-transaminase. This finding corresponds to observations in epileptic animals that the (R)-form exhibits no anticonvulsant effect. 4 Resynthesis of GABA-transaminase, following withdrawal of vigabatrin showed that maximum enzyme activity was obtained within 6 days. This finding corresponds to the persistent effect after withdrawal of the drug in patients, observed in clinical trials. 5 At a concentration of 25 μM, vigabatrin caused a significant increase in the release of endogenous GABA from cultured GABAergic neurons. Although no data on brain levels of the drugs are currently available, judging from vigabatrin blood concentrations in man and from information of brain levels in animals, following chronic treatment, it is conceivable that a sufficiently high concentration of the drug in human brain is obtained to augment GABA release.